Overcoming dormancy of Senna multijuga seeds with an ultrasonic probe the comparison with ultrasound and sulfuric acid baths - Venâncio, Renata Samara Da Silva; Martins, Antonio Cesar Germano (Universidade Federal de Santa Maria, 2019)
ABSTRACT:Understanding germination is extremely important for the production of seedlings that are used in revegetation of degraded areas. Some species enter dormancy as a survival strategy to overcome adverse environmental conditions. Their seeds germinate only when this process is interrupted, which can occur naturally when the conditions become more favorable for the survival of the species or by induction. Studies showed that ultrasound can increase the germination rate of seeds. The objective of this research was to evaluate the effect of an ultrasound probe and compare it with other methodologies implemented for seed germination of Senna multijuga (Rich.) H. S. Irwin & Barneby, a species used in revegetation of degraded areas. The experiment evaluated the effect of the ultrasonic probe at different powers on seeds that were placed to germinate in a gerbox on paper moistened with distilled water. Ninety-five percent of seeds treated with ultrasound and only 14% of non-treated seeds (control) germinated. There was no significant difference in the germination among the treatments with different powers. The speed of germination index (SGI) reached 4.7 in seeds that underwent the treatment, and 0.6 in the control group. From the results it is possible to conclude that the ultrasound probe is an efficient treatment to accelerate seed germination in this species; and consequently, contributed to production of a greater number of seedlings to be used in revegetation of degraded areas in a short period of time.

RESUMO:Entender a germinação é extremamente importante para produção de mudas utilizadas na revegetação de áreas degradadas. Algumas espécies são consideradas dormentes por apresentarem uma estratégia de sobrevivência para superar condições ambientais adversas. Essas sementes germinam apenas quando esse processo é interrompido, o que pode ocorrer naturalmente quando as condições se tornam mais favoráveis para a sobrevivência da espécie ou de forma induzida. Estudos demonstram que o ultrassom pode aumentar a taxa de germinação das sementes. Esse trabalho teve como objetivo avaliar o efeito da sonda ultrassom e compará-la com outras metodologias utilizadas para a germinação de sementes de Senna multijuga (Rich.) H. S. Irwin & Barneby, espécie utilizada na revegetação de áreas degradadas. O experimento avaliou o efeito da sonda de ultrassom em diferentes potências sobre as sementes, que foram colocadas para germinar em gerbox sobre papel umedecido com água destilada. Das sementes que sofreram o tratamento com a sonda de ultrassom 95% germinaram, já das que não sofreram nenhum tratamento apenas 14% delas germinaram. Não houve diferença significativa entre as diferentes potências avaliadas. O índice de velocidade de germinação (IVG) chegou a 4,7 em sementes que sofreram o tratamento e 0,6 no grupo controle. A partir dos resultados é possível concluir que a sonda de ultrassom é um tratamento eficiente para acelerar a germinação de sementes desta espécie e, consequentemente, contribuir para produção de um maior número de mudas em curto período para serem utilizadas na revegetação de áreas degradadas.
Superação da dormência de sementes de Senna multijuga com sonda ultrassônica e a comparação com banho de ultrassom e ácido sulfúrico
Keywords: Senna multijuga (Rich.) H. S. Irwin & Barneby; germination; seeds; ultrasound; revegetation.; Senna multijuga (Rich.) H. S. Irwin & Barneby; germinação; sementes; ultrassom; revegetação.